The correlation salinity and electric voltage - Aminuddin, M.M.M (IEEE Computer Society, 2014)
Oil, gas and coal currently constitute 94% of the total energy generation mix but the increasing demand of electricity, there is a need to be greater diversification of power supply sources in order to tackle the forthcoming electricity crisis. Several studies have started to investigate the feasibility of salt as sources to generate electric. However, the study on the characteristic of salt as electric source has not well documented. Hence, this study investigated the correlation between salinity and electric voltage. Two types of salts were analyzed, i.e., coarse salt and white salt. Based on the results, the generated voltage was linearly increased with the salinity in both types of salt. The finding could be becoming something useful such as a reference to develop a saltwater electric supply or other or to develop a measurement equipment to measure salinity in a liquid.